DIGITAL REPRODUCTIVE HEALTH LITERACY AND REPRODUCTIVE HEALTH BEHAVIOR AMONG FEMALE STUDENTS AT THE FACULTY OF HEALTH SCIENCES, BINA BANGSA UNIVERSITY - Maesaroh Maesaroh; Ade Rahayu Prihartini; Pearly Otis Putri Oktaviani (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Digital media have become one of the main sources of reproductive health information among university students. However, not all information available online is accurate and evidence-based, making digital reproductive health literacy increasingly important. This study aimed to examine the relationship between digital reproductive health literacy and reproductive health behavior among female students at the Faculty of Health Sciences, Bina Bangsa University. This study used a quantitative design with a cross-sectional approach involving 95 first-year female students selected using proportionate stratified random sampling. Data were collected through online questionnaires using the eHealth Literacy Scale (eHEALS) and a reproductive health behavior questionnaire. Data analysis was performed using the Spearman Rank correlation test. The findings revealed that most respondents demonstrated high levels of digital reproductive health literacy (44.2%) and positive reproductive health behavior (42.1%). The Spearman Rank test showed a statistically significant relationship between digital reproductive health literacy and reproductive health behavior (p = 0.000) with a strong positive correlation coefficient (r = 0.740). Digital reproductive health literacy plays an important role in shaping reproductive health behavior among female university students. Strengthening digital-based reproductive health education is necessary to improve students’ ability to evaluate online health information critically and promote healthier reproductive health practices.